Maternal mortality and delivery care under the sentinel model. Case study - Parada-Toro, Irene Margarita; Parada-Toro, Irene; Maldonado-Hernández, Juan; Leyva-López, Ahidée; Márquez-Serrano, Margarita (Horizonte Sanitario, 2022)
Objective: Evaluate the coverage of eutocic delivery care in the Sentinel Unit (UC), of the first level of care, verify compliance with what is established in the model and identify the factors that prevent or favor its use, from the perspective of the providers of health and users.Materials and methods: Qualitative and quantitative study, retrospective with information on the primary and secondary bases. Main variable: care of eutocic delivery. Analysis: Descriptive, percentages for categorical variables and δ means for continuous variables, statistical differences between two categorical variables, Pearson Chi2. Multivariate: logistic regression of factors associated with delivery care. Twelve semi-structured interviews were conducted with users and 8 service providers, the analysis was carried out based on Grounded Theory through Ethnograph v.5.Results: Sample: 218 users, average age was 24.7 years. The UC provided prenatal control, 61% more than 5 consultations; however, the care of eutocic deliveries was only 17 deliveries (33.4%). The most important barriers referred to by the users and health providers were: lack of personnel, training, supplies and insufficient support and institutional legal protection in case of complications.Conclusions: UC is a strategy to return delivery care to the first level of care, but it is necessary to implement a plan to improve and strengthen providers.Keywords: Maternal mortality; Normal delivery; Access to health care; Health personnel; Prenatal care.